Pastoralists’ perception of the impact of East Coast fever on cattle production under extensive management in Northern Rift Valley, Kenya - Kipronoh, K.A.; Gathuma, J.M.; Kitala, P.M.; Kiara, Henry K. (2011)
A study using participatory epidemiology (PE) methodologies was conducted in West Pokot and Baringo districts, Northern Rift Valley, Kenya to assess the status of East Coast Fever (ECF) and obtain livestock keepers’ perceptions of how the disease impacts on their livelihoods. A total of 658 livestock keepers comprising of 480 men and 178 women were invited to participate in community meetings held in twenty two purposively selected locations each in West Pokot and Baringo. Fifty six percent of the livestock keepers were from West Pokot while the remaining 54 percent were from Baringo District. Nearly all the households in both communities depended on cattle keeping as the major source of livelihood. The activity was ranked as priority enterprise by 96.2% and 93.3% of the groups in West Pokot and Baringo district respectively. Cattle diseases were identified as the main constraint affecting production and in particular, ECF and trypanosomosis were reported as the most important compared to other diseases. The informants were relatively consistent in estimating the impact of cattle diseases on derived benefits. There was good agreement among the various groups with coefficient of concordance (W) values ranging between 0.43 and 0.60 (p < 0:05 – p < 0.01). East Coast fever was found to have the greatest impact. Based on the findings from this study, there is need for stakeholders in the livestock industry to develop control strategies for ECF control that are supportive to the production system in a particular the region.